CHRONIC HEPATITIS B CAUSED BY HEPATITIS B VIRUS MUTANTS AND ITS CLINICAL AND LABORATORY CHARACTERISTICS - Oblokulov A.R,; Bakhronov О.O., (TADQIQOTLAR, 2025)
Abstract Chronic hepatitis B remains a major global health concern due to its potential progression to liver cirrhosis and hepatocellular carcinoma. In recent years, increasing attention has been directed toward hepatitis B virus (HBV) mutant strains, particularly precore and basal core promoter mutations, which are associated with HBeAg-negative chronic hepatitis B and pose significant diagnostic and therapeutic challenges.